PVC pipe composition and preparation method of PVC pipe

By combining PVC resin and PE resin, and loading zinc oxide and manganese oxide on the concave and convex rod soil, combining 4-carboxyphenylboric acid and acrylate, the problem of insufficient mechanical properties and flame retardant properties of PVC pipes is solved, and higher flame retardant properties and mechanical properties are achieved, which is suitable for modern building safety standards.

CN119912768AActive Publication Date: 2025-05-02ZHEJIANG BANGDE PIPE IND

Patent Information

Application Number
CN202510421295.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-05-02
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

Existing PVC pipes have shortcomings in terms of mechanical properties and flame retardant properties, which are difficult to meet the needs of modern building safety standards.

Method used

PVC resin and PE resin are used to combine, and the composite metal oxide is formed by loading zinc oxide and manganese oxide on the concave and convex rod soil, and then components such as 4-carboxyphenylboric acid and acrylate are introduced to form a B-O-B crosslinking network structure and a flexible alkyl long chain structure to improve flame retardant performance and mechanical properties.

Benefits of technology

It significantly improves the flame retardant and mechanical properties of PVC pipes, can better meet the needs of modern building safety standards, and shows good aging resistance in humid and hot environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of PVC pipe production and processing, and particularly discloses a PVC pipe composition and a preparation method of a PVC pipe. PVC resin and PE resin are compounded, the problem of PVC decomposition caused by high temperature in the processing process is reduced, meanwhile, the PE resin has good flexibility, and by compounding the PVC resin and the PE resin, the PVC resin and the PE resin have good flexibility, so that the PVC pipe composition is more stable in performance. The mechanical property of the PVC pipe can be improved; 4-carboxyphenylboronic acid in the composite modified attapulgite provided by the invention forms a B-O-B cross-linked network structure at a high temperature, the 4-carboxyphenylboronic acid can have a synergistic effect with composite metal oxides (zinc oxide and manganese oxide), the thermal stability and compactness of a carbon layer are improved, and the flame retardant property of the PVC pipe is further improved; a flexible alkyl long-chain structure is formed through copolymerization of 1, 4-diol, reversible deformation occurs under the action of external force, and the mechanical property of the PVC pipe is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC pipe production and processing, and in particular to a PVC pipe composition and a preparation method of the PVC pipe. Background Art

[0002] Polyvinyl chloride (PVC) pipes are made of polyvinyl chloride resin as the main raw material. They have the advantages of light weight, high mechanical strength, chemical corrosion resistance, good electrical insulation, long life and low cost. Therefore, they are widely used in the fields of construction, electricity and communications. However, the current production process with pure PVC resin as the main material has obvious shortcomings. Although it has been improved by adding auxiliary materials and plasticizers, the resulting pipes still generally have insufficient plasticity and are difficult to meet the requirements of material flexibility in most production scenarios.

[0003] In the current production process, a large amount of additives such as plasticizers and stabilizers need to be added. These ingredients will significantly weaken the flame retardant properties of polyvinyl chloride materials. With the improvement of modern building safety standards, especially in environments with higher fire risks, the flame retardancy of traditional PVC pipes has gradually been unable to meet market demand.

[0004] Although pure PVC resin as the main material can guarantee basic performance, the high cost of raw materials has prompted companies to seek alternatives, and simple additive formulation cannot completely solve the problems of poor mechanical properties and insufficient flame retardancy. How to break through the existing limitations through material modification or process innovation has become a key issue in promoting the upgrading of the PVC pipe industry.

[0005] Chinese patent document CN202110397226.X discloses a PVC composition, a preparation method and an application thereof. The composition includes the following components calculated by weight: 80 to 100 parts of polyvinyl chloride resin; 40 to 80 parts of calcium carbonate; 0.5 to 1.0 parts of high melting point polyethylene wax; 0.5 to 1.0 parts of paraffin; 2 to 8 parts of toughening agent; 2 to 4 parts of organic tin stabilizer; the prepared composition has the characteristics of low friction coefficient, good mechanical properties, acid and alkali resistance and corrosion resistance, but the flame retardant properties still need to be further improved. Summary of the invention

[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a PVC pipe composition and a method for preparing the PVC pipe.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme: A PVC pipe material composition comprises the following raw materials in parts by weight: 60-80 parts of PVC resin, 20-30 parts of PE resin, 15-25 parts of composite modified attapulgite, 10-20 parts of compatibilizer, 4-6 parts of heat stabilizer, 5-10 parts of lubricant, 1-3 parts of antioxidant and 1-2 parts of ultraviolet absorber.

[0008] In the technical solution disclosed in the present invention, the preparation method of the composite modified attapulgite is as follows: S1. Dissolving zinc nitrate and manganese nitrate in deionized water, then adding attapulgite thereto, uniformly dispersing by ultrasonication, then adding oxalic acid solution thereto, stirring, filtering, washing, drying, and calcining to obtain an attapulgite composite; S2, dispersing the attapulgite composite in an ethanol aqueous solution, then adding vinyltriethoxysilane thereto, stirring for reaction, and then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Dispersing the double-bond modified attapulgite composite in an organic solvent, then adding acrylate, 2-butene-1,4-diol and an initiator thereto, heating and stirring the reaction under a nitrogen atmosphere, and after the reaction is completed, adding 4-carboxyphenylboric acid and a catalyst thereto, and continuing the reaction, and after the reaction is completed, filtering, washing and drying to obtain the composite modified attapulgite.

[0009] Specifically, in step S1, the mass ratio of zinc nitrate, manganese nitrate, attapulgite and oxalic acid solution is 2-4:2-4:10-15:20-30.

[0010] More specifically, the concentration of the oxalic acid solution is 0.5-2 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0011] Specifically, in step S1, the stirring temperature is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C, and 70°C can be selected; the stirring time is 4-8h, for example, 4h, 5h, 6h, 7h, and 8h can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0012] Specifically, in step S1, the calcination temperature is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C, and 1000°C can be selected; the calcination time is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, and 4h can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] Specifically, in step S2, the mass ratio of the attapulgite composite and vinyltriethoxysilane is 10-15:1-3, for example, 10:1, 10:2, 10:3, 12:1, 12:2, 12:3, 15:1, 15:2, 15:3 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Specifically, in step S3, the mass ratio of the double-bond modified attapulgite composite, acrylate, 2-butene-1,4-diol, initiator, 4-carboxyphenylboric acid and catalyst is 10-20:3-6:3-6:1-2:3-5:1-2.

[0015] More specifically, the number of carbon atoms of the acrylic acid ester is ≥10, and for example, lauryl acrylate, lauryl methacrylate, and octadecyl acrylate may be selected.

[0016] More specifically, the initiator is selected from benzoyl peroxide or azobisisobutyronitrile.

[0017] More specifically, the catalyst is selected from 4-dimethylaminopyridine.

[0018] In the technical solution disclosed in the present invention, the compatibilizer is selected from ethylene vinyl acetate grafted maleic anhydride or polyethylene grafted maleic anhydride.

[0019] In the technical solution disclosed in the present invention, the heat stabilizer is selected from a calcium zinc heat stabilizer or an organic tin heat stabilizer.

[0020] In the technical solution disclosed in the present invention, the lubricant is selected from one or more of calcium stearate, polyethylene wax, stearic acid, and stearic acid monoglyceride.

[0021] In the technical solution disclosed in the present invention, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, and antioxidant DLTDP.

[0022] In the technical solution disclosed in the present invention, the ultraviolet absorber is selected from one or more of titanium dioxide, UV328, UV327, and UV326.

[0023] The present invention also provides a method for preparing a PVC pipe, comprising the following steps: adding the raw materials of the PVC pipe composition into a high-speed mixer according to the formula ratio and mixing them evenly, then extruding and granulating them in a twin-screw extruder, and then cooling and shaping them to obtain the PVC pipe.

[0024] More specifically, the mixing speed in the high-speed mixer is 1000-1500 r / min, the mixing time is 5-15 min, and the mixing temperature is 100-120°C.

[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses PVC resin and PE resin for compounding. The addition of PE resin can significantly improve the fluidity of the PVC resin melt, reduce the processing temperature requirement, and reduce the problem of PVC decomposition caused by high temperature during processing. At the same time, PE resin also has good flexibility. By compounding PVC resin and PE resin, the mechanical properties of PVC pipes can be improved.

[0026] (2) The present invention first loads zinc oxalate and manganese oxalate on the surface of attapulgite, and then calcines the mixture to form a composite metal oxide of zinc oxide and manganese oxide on the surface of the attapulgite. Then, double bonds are introduced into the surface of the attapulgite composite, and acrylate and 2-butene-1,4-diol are grafted onto the surface of the attapulgite composite through an addition reaction between the double bonds. Finally, under the action of a catalyst, 4-carboxyphenylboric acid and 2-butene-1,4-diol undergo an esterification reaction to obtain a composite modified attapulgite. The 4-carboxyphenylboric acid in the composite modified attapulgite provided by the present invention forms a BOB cross-linked network structure at high temperature, and can react with the composite metal oxide (zinc oxide, manganese oxide) to form a borate glass layer. The composite carbon layer has higher thermal stability and density, can effectively block oxygen and heat, and the 4-carboxyphenylboric acid and the composite metal oxide act synergistically to jointly improve the flame retardant properties of the PVC pipe.

[0027] (3) In the composite modified attapulgite provided by the present invention, acrylate and 2-butene-1,4-diol are copolymerized to form a flexible alkyl long-chain structure, which significantly reduces the rigidity of the PVC resin material and improves the impact resistance of the material; at the same time, the flexibility of the alkyl long chain enables the PVC molecular chain to undergo reversible deformation under the action of external force, delaying fracture through segment slip and microcrack passivation, further improving the mechanical properties of the PVC pipe; in addition, the hydrophobic alkyl long-chain structure and the benzene ring structure in 4-carboxyphenylboronic acid show good aging resistance under wet and hot conditions, so that the PVC pipe can also show good stability under wet and hot conditions, and can resist the erosion of wet and hot environments and delay the aging process. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0029] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0030] The brand of the PVC resin used in the embodiments of the present invention is SG-5, purchased from Zibo Anhao Chemical Co., Ltd.; the brand of the PE resin is PE6004, CAS number: 25135-73-3; the mesh number of the attapulgite is 200 mesh; the brand of ethylene vinyl acetate grafted maleic anhydride is Bynel 3810; the brand of polyethylene grafted maleic anhydride is DuPont 41E710; the CAS number of the calcium zinc heat stabilizer is 1592-23-0.

[0031] Example 1

[0032] A method for preparing a PVC pipe comprises the following steps: 60 parts of PVC resin, 20 parts of PE resin, 15 parts of composite modified attapulgite, 10 parts of compatibilizer ethylene vinyl acetate grafted maleic anhydride, 4 parts of calcium zinc heat stabilizer, 5 parts of stearic acid, 1 part of antioxidant 168 and 1 part of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, granulation is performed in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, and the head temperature is set to 165°C. After cooling and shaping, the PVC pipe is obtained.

[0033] Wherein, the preparation method of the composite modified attapulgite is as follows: S1. Dissolve 2 g of zinc nitrate and 2 g of manganese nitrate in 150 mL of deionized water, then add 10 g of attapulgite, disperse uniformly by ultrasonication, add 20 g of 1 mol / L oxalic acid solution, stir at 60 ° C for 6 h, filter, wash, dry, and calcine at 900 ° C for 3 h to obtain an attapulgite composite; S2, dispersing 10 g of the attapulgite composite in 150 mL of 80 wt% ethanol aqueous solution, then adding 1 g of vinyltriethoxysilane thereto, stirring at room temperature for 2 h, then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Disperse 10g of the double-bond modified attapulgite composite in 150mL of the organic solvent DMF, then add 3g of lauryl acrylate, 3g of 2-butene-1,4-diol and 1g of initiator azobisisobutyronitrile, heat and stir to react for 3h at 75°C in a nitrogen atmosphere, after the reaction is completed, add 3g of 4-carboxyphenylboric acid and 1g of catalyst 4-dimethylaminopyridine, and continue to react at 75°C for 2h. After the reaction is completed, filter, wash and dry to obtain the composite modified attapulgite.

[0034] Example 2

[0035] A method for preparing a PVC pipe comprises the following steps: 80 parts of PVC resin, 30 parts of PE resin, 25 parts of composite modified attapulgite, 20 parts of compatibilizer polyethylene grafted maleic anhydride, 6 parts of calcium zinc heat stabilizer, 4 parts of stearic acid, 4 parts of polyethylene wax, 2 parts of antioxidant 1010 and 2 parts of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, granulation is performed in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, the head temperature is set to 165°C, and then cooled and formed to obtain a PVC pipe.

[0036] Wherein, the preparation method of the composite modified attapulgite is as follows: S1. Dissolve 4 g of zinc nitrate and 2 g of manganese nitrate in 150 mL of deionized water, then add 12 g of attapulgite, disperse uniformly by ultrasonication, add 20 g of 1 mol / L oxalic acid solution, stir at 60 ° C for 6 h, filter, wash, dry, and calcine at 900 ° C for 3 h to obtain an attapulgite composite; S2, dispersing 12 g of the attapulgite composite in 150 mL of 80 wt% ethanol aqueous solution, then adding 2 g of vinyltriethoxysilane thereto, stirring at room temperature for 2 h, then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Disperse 15g of the double-bond modified attapulgite composite in 150mL of the organic solvent DMF, then add 4g of lauryl acrylate, 4g of 2-butene-1,4-diol and 1.5g of initiator azobisisobutyronitrile, and heat and stir to react for 3h at 75°C in a nitrogen atmosphere. After the reaction is completed, add 4g of 4-carboxyphenylboric acid and 1.5g of catalyst 4-dimethylaminopyridine, and continue to react at 75°C for 2h. After the reaction is completed, filter, wash and dry to obtain the composite modified attapulgite.

[0037] Example 3

[0038] A method for preparing a PVC pipe comprises the following steps: 65 parts of PVC resin, 25 parts of PE resin, 20 parts of composite modified attapulgite, 15 parts of compatibilizer polyethylene grafted maleic anhydride, 5 parts of calcium zinc heat stabilizer, 6 parts of stearic acid monoglyceride, 4 parts of polyethylene wax, 3 parts of antioxidant 1010 and 2 parts of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, the granulation is performed in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, the head temperature is set to 165°C, and then cooled and formed to obtain a PVC pipe.

[0039] Wherein, the preparation method of the composite modified attapulgite is as follows: S1. Dissolve 2 g of zinc nitrate and 4 g of manganese nitrate in 150 mL of deionized water, then add 15 g of attapulgite, disperse uniformly by ultrasonication, add 20 g of 1 mol / L oxalic acid solution, stir at 60 ° C for 6 h, filter, wash, dry, and calcine at 900 ° C for 3 h to obtain an attapulgite composite; S2, dispersing 15 g of the attapulgite composite in 150 mL of 80 wt% ethanol aqueous solution, then adding 3 g of vinyltriethoxysilane thereto, stirring at room temperature for 2 h, then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Disperse 20g of the double-bond modified attapulgite composite in 150mL of the organic solvent DMF, then add 6g of lauryl acrylate, 6g of 2-butene-1,4-diol and 2g of initiator azobisisobutyronitrile, heat and stir to react for 3h at 75°C in a nitrogen atmosphere, after the reaction is completed, add 5g of 4-carboxyphenylboric acid and 2g of catalyst 4-dimethylaminopyridine, continue to react at 75°C for 2h, after the reaction is completed, filter, wash and dry to obtain the composite modified attapulgite.

[0040] Comparative Example 1

[0041] A method for preparing a PVC pipe comprises the following steps: 65 parts of PVC resin, 25 parts of PE resin, 20 parts of attapulgite, 15 parts of compatibilizer polyethylene grafted maleic anhydride, 5 parts of calcium zinc heat stabilizer, 6 parts of stearic acid monoglyceride, 4 parts of polyethylene wax, 3 parts of antioxidant 1010 and 2 parts of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, the granulation is performed by extrusion in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, the head temperature is set to 165°C, and then cooled and formed to obtain a PVC pipe.

[0042] Compared with Example 3, Comparative Example 1 did not perform modification treatment on the attapulgite.

[0043] Comparative Example 2

[0044] A method for preparing a PVC pipe comprises the following steps: 65 parts of PVC resin, 25 parts of PE resin, 20 parts of composite modified attapulgite, 15 parts of compatibilizer polyethylene grafted maleic anhydride, 5 parts of calcium zinc heat stabilizer, 6 parts of stearic acid monoglyceride, 4 parts of polyethylene wax, 3 parts of antioxidant 1010 and 2 parts of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, the granulation is performed in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, the head temperature is set to 165°C, and then cooled and formed to obtain a PVC pipe.

[0045] Wherein, the preparation method of the composite modified attapulgite is as follows: S1, dispersing 15g of attapulgite in 150mL of 80wt% ethanol aqueous solution, then adding 3g of vinyltriethoxysilane thereto, stirring at room temperature for 2h, then filtering, washing and drying to obtain double-bond modified attapulgite; S2. Disperse 20 g of double-bond modified attapulgite in 150 mL of organic solvent DMF, then add 6 g of lauryl acrylate, 6 g of 2-butene-1,4-diol and 2 g of initiator azobisisobutyronitrile, heat and stir to react for 3 h at 75 ° C in a nitrogen atmosphere. After the reaction is completed, add 5 g of 4-carboxyphenylboric acid and 2 g of catalyst 4-dimethylaminopyridine, and continue to react at 75 ° C for 2 h. After the reaction is completed, filter, wash and dry to obtain composite modified attapulgite.

[0046] Compared with Example 3, in Comparative Example 2, zinc oxide and manganese oxide were not loaded on the attapulgite.

[0047] Comparative Example 3

[0048] A method for preparing a PVC pipe comprises the following steps: 65 parts of PVC resin, 25 parts of PE resin, 20 parts of composite modified attapulgite, 15 parts of compatibilizer polyethylene grafted maleic anhydride, 5 parts of calcium zinc heat stabilizer, 6 parts of stearic acid monoglyceride, 4 parts of polyethylene wax, 3 parts of antioxidant 1010 and 2 parts of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, the granulation is performed in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, the head temperature is set to 165°C, and then cooled and formed to obtain a PVC pipe.

[0049] Wherein, the preparation method of the composite modified attapulgite is as follows: S1. Dissolve 2 g of zinc nitrate and 4 g of manganese nitrate in 150 mL of deionized water, then add 15 g of attapulgite, disperse uniformly by ultrasonication, add 20 g of 1 mol / L oxalic acid solution, stir at 60 ° C for 6 h, filter, wash, dry, and calcine at 900 ° C for 3 h to obtain an attapulgite composite; S2, dispersing 15 g of the attapulgite composite in 150 mL of 80 wt% ethanol aqueous solution, then adding 3 g of vinyltriethoxysilane thereto, stirring at room temperature for 2 h, then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Disperse 20g of the double-bond modified attapulgite composite in 150mL of the organic solvent DMF, then add 6g of 2-butene-1,4-diol and 2g of initiator azobisisobutyronitrile, heat and stir to react for 3h at 75°C in a nitrogen atmosphere, after the reaction is completed, add 5g of 4-carboxyphenylboric acid and 2g of catalyst 4-dimethylaminopyridine, and continue to react at 75°C for 2h. After the reaction is completed, filter, wash and dry to obtain the composite modified attapulgite.

[0050] Compared with Example 3, Comparative Example 3 does not introduce lauryl acrylate.

[0051] Comparative Example 4

[0052] A method for preparing a PVC pipe comprises the following steps: 65 parts of PVC resin, 25 parts of PE resin, 20 parts of composite modified attapulgite, 15 parts of compatibilizer polyethylene grafted maleic anhydride, 5 parts of calcium zinc heat stabilizer, 6 parts of stearic acid monoglyceride, 4 parts of polyethylene wax, 3 parts of antioxidant 1010 and 2 parts of ultraviolet absorber UV327 are added to a high-speed mixer and mixed evenly. The mixing speed in the high-speed mixer is 1000r / min, the mixing time is 10min, and the mixing temperature is 120°C. Subsequently, the granulation is performed in a twin-screw extruder. The temperature of the extruder zone 1 is set to 195°C, the temperature of the zone 2 is set to 190°C, the zone 3 is set to 180°C, the zone 4 is set to 175°C, the zone 5 is set to 170°C, the head temperature is set to 165°C, and then cooled and formed to obtain a PVC pipe.

[0053] Wherein, the preparation method of the composite modified attapulgite is as follows: S1. Dissolve 2 g of zinc nitrate and 4 g of manganese nitrate in 150 mL of deionized water, then add 15 g of attapulgite, disperse uniformly by ultrasonication, add 20 g of 1 mol / L oxalic acid solution, stir at 60 ° C for 6 h, filter, wash, dry, and calcine at 900 ° C for 3 h to obtain an attapulgite composite; S2, dispersing 15 g of the attapulgite composite in 150 mL of 80 wt% ethanol aqueous solution, then adding 3 g of vinyltriethoxysilane thereto, stirring at room temperature for 2 h, then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Disperse 20 g of the double-bond modified attapulgite composite in 150 mL of the organic solvent DMF, then add 6 g of lauryl acrylate, 6 g of 2-butene-1,4-diol and 2 g of initiator azobisisobutyronitrile, heat and stir to react for 3 h at 75 °C in a nitrogen atmosphere, and after the reaction is completed, filter, wash and dry to obtain the composite modified attapulgite.

[0054] Compared with Example 3, Comparative Example 4 does not introduce 4-carboxyphenylboronic acid.

[0055] The PVC pipes prepared in Examples 1-3 and Comparative Examples 1-4 were made into specimens that met the test specifications, and then performance tests were performed, as follows: Tensile strength test: Tested in accordance with standard GB / T 1040.2-2022, tested 3 times in parallel, and the results were averaged; Impact resistance test: Tested in accordance with standard GB / T 1043.2-2018, tested three times in parallel, and the results were averaged; Limiting oxygen index test: Tested in accordance with standard GB / T 2406.2-2009, tested three times in parallel, and the results were averaged; Moisture and heat resistance test: The specimens were placed in an environment of 85°C and 90% relative humidity, taken out after 1000 hours, and the tensile strength retention rate was tested.

[0056] The test results are shown in Table 1.

[0057] Table 1 Performance test results of different embodiments and comparative examples

[0058] As can be seen from Table 1, in Comparative Example 2, zinc oxide and manganese oxide were not loaded on attapulgite, and the flame retardant performance was significantly reduced. In Comparative Example 3, lauryl acrylate was not introduced, and in Comparative Example 4, 4-carboxyphenylboric acid was not introduced. The mechanical properties and moisture and heat resistance were significantly inferior to those of the embodiments of the present invention. The PVC pipe prepared in the embodiments of the present invention has excellent mechanical properties, flame retardant properties and moisture and heat aging resistance.

[0059] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A PVC pipe composition, characterized in that: The raw materials include the following components in parts by weight: 60-80 parts of PVC resin, 20-30 parts of PE resin, 15-25 parts of composite modified attapulgite, 10-20 parts of compatibilizer, 4-6 parts of heat stabilizer, 5-10 parts of lubricant, 1-3 parts of antioxidant and 1-2 parts of ultraviolet absorber.

2. The PVC pipe composition according to claim 1, characterized in that: The preparation method of the composite modified attapulgite is as follows: S1. Dissolving zinc nitrate and manganese nitrate in deionized water, then adding attapulgite thereto, uniformly dispersing by ultrasonication, then adding oxalic acid solution thereto, stirring, filtering, washing, drying, and calcining to obtain an attapulgite composite; S2, dispersing the attapulgite composite in an ethanol aqueous solution, then adding vinyltriethoxysilane thereto, stirring for reaction, and then filtering, washing, and drying to obtain a double-bond modified attapulgite composite; S3. Dispersing the double-bond modified attapulgite composite in an organic solvent, then adding acrylate, 2-butene-1,4-diol and an initiator thereto, heating and stirring the reaction under a nitrogen atmosphere, and after the reaction is completed, adding 4-carboxyphenylboric acid and a catalyst thereto, and continuing the reaction, and after the reaction is completed, filtering, washing and drying to obtain the composite modified attapulgite.

3. The PVC pipe composition according to claim 2, characterized in that: In step S1, the mass ratio of zinc nitrate, manganese nitrate, attapulgite and oxalic acid solution is 2-4:2-4:10-15:20-30, wherein the concentration of the oxalic acid solution is 0.5-2 mol / L.

4. The PVC pipe composition according to claim 2, characterized in that: In step S2, the mass ratio of the attapulgite composite to vinyltriethoxysilane is 10-15:1-3.

5. The PVC pipe composition according to claim 2, characterized in that: In step S3, the mass ratio of the double-bond modified attapulgite composite, acrylate, 2-butene-1,4-diol, initiator, 4-carboxyphenylboric acid and catalyst is 10-20:3-6:3-6:1-2:3-5:1-2.

6. The PVC pipe composition according to claim 2, characterized in that: In step S3, the number of carbon atoms of the acrylic acid ester is ≥10.

7. The PVC pipe composition according to claim 2, characterized in that: In step S3, the initiator is selected from benzoyl peroxide or azobisisobutyronitrile, and the catalyst is selected from 4-dimethylaminopyridine.

8. The PVC pipe composition according to claim 1, characterized in that: The compatibilizer is selected from ethylene vinyl acetate grafted maleic anhydride or polyethylene grafted maleic anhydride; The heat stabilizer is selected from calcium zinc heat stabilizer or organic tin heat stabilizer; The lubricant is selected from one or more of calcium stearate, polyethylene wax, stearic acid, and stearic acid monoglyceride.

9. The PVC pipe composition according to claim 1, characterized in that: The antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, and antioxidant DLTDP; The ultraviolet absorber is selected from one or more of titanium dioxide, UV328, UV327, and UV326.

10. A method for preparing a PVC pipe, characterized in that: The method comprises the following steps: adding the raw materials of the PVC pipe material composition according to any one of claims 1 to 9 into a high-speed mixer and mixing them uniformly according to the formula ratio, then extruding and granulating them in a twin-screw extruder, and cooling and shaping them to obtain the PVC pipe material.

Citation Information

Patent Citations

  • A PVC composition, its preparation method and application

    CN113045843B

  • Polyvinyl chloride tube containing modified attapulgite and preparing method thereof

    CN103059456A

  • Modified nano silicon dioxide, preparation method thereof, pigment dispersoid, and photosensitive resin composition

    CN103497543A

  • Compression-resistant and impact-resistant HPVC pipe and preparation process thereof

    CN117645765A

  • Wear-resistant and impact-resistant composite PVC (polyvinyl chloride) material and preparation method thereof

    CN119591998A

Cited By

  • High-impact PVC (polyvinyl chloride) pipe aggregate and preparation method thereof

    CN120623676A

  • COF nanosheet for enhancing flame retardant property of PVC (polyvinyl chloride) and PE (polyethylene) pipes as well as preparation method and application of COF nanosheet

    CN120647959A

  • COF nanosheet for enhancing flame retardant performance of PVC and PE pipes, and preparation method and application thereof

    CN120647959B

  • PVC pipe composition and preparation method of PVC pipe

    CN121249067A

  • High-temperature-resistant PVC (polyvinyl chloride) pipe and manufacturing process thereof

    CN122213573A